The paradoxical nexus between corporate social responsibility and sustainable financial performance: Evidence from the international construction business. (10th April 2018) - Lu, Weisheng; Ye, Meng; Chau, K.W.; Flanagan, Roger
Abstract: The aim of the research is to substantiate the hypothesis of a paradoxical dynamic link between corporate social responsibility (CSR) and its material implications including sustainable corporate financial performance (CFP). By analysing a panel of 67 international construction companies from 2006 to 2015, we found that CSR programs can be detrimental to CFP in the short term but conducive to improving it in the long term. The findings of this research indicate that, in the international construction business, the impact of CSR on CFP is not immediate and unchanging, and it takes time to materialize CSR for sustainable development. A significant practical use of this research is to provide evidence for the assertion that business stakeholders should be relieved from short‐termism in assuming social responsibility. Further research is recommended to test this support in a more general business setting towards developing a general theory on CSR and sustainable development.